MENGALISIS GAMBAR PADA PENARI SUKU MOI KELIM MENGGUNAKAN PENDEKATAN SEMIOTIK - Gifelem, Agustinus Gideon (SOSCIED, 2024)
The purpose of this study is to find out and describe the meaning and significance of the images on the bodies of Moi Kelim tribal dancers. The method used in this study is a qualitative method. The source used in this study is that the researcher obtained from a direct interview with Mr. Iskandar Osok as the head of the Malaloi Studio. The data collection technique used is interview, while the data analysis technique used in the research is the flow analysis model technique, which includes three components, namely: data reduction, data presentation and conclusion drawn. The results of the research on the images on the bodies of the Moi Kelim tribal dancers have three semiotic elements, namely: icons, indexes and symbols. The total data obtained by the researcher in analyzing the images on the bodies of the Moi Kelim tribal dancers was fourteen data consisting of eight icons, four indexes, and two symbols